Potential of rainwater harvesting in wilayah persekutuan Malaysia - Ratnasari, Anisa; Bhaskara Adiprabowo, Arya; Gilang Al Afgani, Andhika; Widiyanti, Atik; Oktavia, Lily (Universitas Nahdlatul Ulama Surabaya, 2022)
Although Malaysia has abundant water resources, some parts of Malaysia are currently facing water shortage problems. The increasing demand for water has sparked initiatives to seek alternative water supplies. Rainwater harvesting has been proposed by governments as part of the solution to alleviate the problem of water scarcity. Literature related to rainwater harvesting is available from a variety of sources. In this study, rainfall was analysed as a crucial factor affecting RWHS efficiency, rainwater potential at different zones for residential, industrial, and commercial. In addition, the study evaluated the rainwater quality that obtain fresh rainfall and roof rainfall. Furthermore, potential of treatment technology for rainwater was suggested to optimate rainwater harvesting.